The paradox of peril: The impact of health worker mortality rates during the COVID-19 pandemic on nursing and medical students' motivation - Kezia Mirella Yung; Andini Dwy Pramisti; Claudia Hilda Putri (Public Health Risk Assesment Journal, 2026)
Background: The COVID-19 pandemic has precipitated an unprecedented crisis within the global healthcare workforce, characterized by high morbidity and mortality rates among frontline professionals. In Indonesia, the mortality rate of health workers reached critical levels, raising concerns about the future sustainability of the healthcare system and the psychological readiness of medical and nursing students. Previous studies have highlighted the dual impact of crisis exposure on career motivation; either acting as a deterrent due to fear or as a catalyst due to altruism. However, few have specifically quantified the correlation between awareness of mortality rates and motivation among Indonesian students. Methods: This study utilized a quantitative correlational approach with a cross-sectional design to investigate the relationship between awareness of health worker mortality rates and the motivation to pursue a healthcare career. A simple random sampling technique was employed to recruit 128 medical and nursing students from various accredited institutions in Indonesia, with data collected via a structured online questionnaire and analyzed using the Spearman correlation test. Findings: The statistical analysis revealed a significant positive correlation (p < 0.05) between students' awareness of high mortality rates and their motivation to become health workers, contradicting the hypothesis that increased risk perception would diminish career interest. These findings align with the terror management theory and the concept of prosocial motivation, suggesting that exposure to mortality salience in a professional context may trigger a "heroic" or altruistic response rather than avoidance behaviors. Conclusion: High mortality rates among health workers during the pandemic paradoxically strengthened the motivation of medical and nursing students, indicating a resilient and duty-driven generation of future health professionals. Novelty/Originality of this article: This study offers new insights into the psychological resilience of health students in developing nations, challenging conventional assumptions about risk aversion in career planning during health crises.